Nilai Entrance Skin Dose Tiroid antara menggunakan Thyroid Shield dan tanpa Thyroid Shield pada Pemeriksaan CT Scan Kepala - Angga Yosainto Bequet; Panji Wibowo Nurcahyo; Susi Tri Isnoviasih (Poltekkes Kemenkes Semarang, 2024)
Background: CT scans have a much greater dose than conventional radiographic examinations. The thyroid organ is an organ that is sensitive to radiation which is located near the head, precisely in the inferior part of the head so that when a CT scan of the head is carried out, the thyroid organ will be exposed to radiation. The aim of this study was to determine the difference in thyroid skin dose entry value between using a thyroid shield and without a thyroid shield on a head CT scan.Methods: This study is a type of quantitative research with a pre-experimental design. The object of research is Entrance Skin Dose (ESE) of ThyroidOrgan on non-contrast head CT Scan examination. The research location is at the Radiology Department at the Regional General Hospital Prof. Dr. Margono Soekarjo Purwokerto. Sample data number is 50 people (25 samples of non-contrast head CT scans without thyroid shield, and 25 samples of non-contrast head CT scans with thyroid shield. Data was obtained by measuring the radiation dose using a dosimeter placed over the thyroid area during a non-contrast CT scan between using a thyroid shield and without using a thyroid shield. Data analysis was performed using statistical tests Results: The results of measuring the radiation dose to the samples showed that the average radiation dose to the skin surface of the thyroid organ on a non-contrast CT scan without using a thoracic shield was 884.96 µSv and using a thyroid shield was 428.64 µSv. This shows that the average radiation dose from the skin surface of the thyroid organ decreased by 456.32 µSv (51.56%).Conclusions: There is a significant difference in the amount of radiation dose to the surface of the skin of the thyroid organ in non-contrast head CT scans between using a thyroid shield and without using a shield with a dose reduction of 51.6% of the radiation dose without using a thyroid shield.